Bridging Collaborative Practices with Digital Transformation: Mapping Trends in Madrasah Leadership - Ahmad Ridani; Siti Julaiha; Chairul Anwar; M. Ainur Rofiq (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Digital transformation has intensified the need for educational leadership models that integrate technological adaptation with collaborative organizational practices. This study aims to map research trends in collaborative practices, digital transformation, and madrasah leadership, and to identify conceptual gaps and future research directions. A scoping review design was employed using literature retrieved from the Scopus and Web of Science databases. Peer-reviewed journal articles published between 2015 and 2025 were selected through systematic screening and analyzed through evidence mapping, data charting, and thematic synthesis. The findings indicate a substantial increase in publications on collaborative leadership and digital transformation; however, studies specifically addressing madrasah leadership remain limited. The review also reveals that collaborative practices and digital transformation are frequently examined separately, creating a gap in understanding their integration within Islamic educational institutions. This study contributes a conceptual framework that bridges collaborative practices and digital transformation to support adaptive madrasah leadership and sustainable institutional development. Future studies should empirically validate the proposed framework in diverse madrasah contexts.